Molecular and Biological Characterization of a New Strawberry Cytorhabdovirus - Jana Fránová; Jaroslava Přibylová; Igor Koloniuk (Viruses, 2019)
Virus diseases of strawberry present several complex problems. More than 25 viruses have been described in the genus Fragaria thus far. Here, we describe a novel rhabdovirus, tentatively named strawberry virus 1 (StrV-1), that infects F. ananassa and F. vesca plants. Genomic sequences of three distinct StrV-1 genotypes co-infecting a single F. ananassa host were obtained using combined Illumina and Ion Proton high-throughput sequencing. StrV-1 was transmitted to herbaceous plants via Aphis fabae and A. ruborum, further mechanically transmitted to Nicotiana occidentalis 37B and sub-inoculated to N. benthamiana, N. benthamiana DCL2/4i, N. occidentalis 37B, and Physalis floridana plants. Irregular chlorotic sectors on leaf blades and the multiplication of calyx leaves seem to be the diagnostic symptoms for StrV-1 on indexed F. vesca clones. StrV-1 was detected in asymptomatic grafted plants and in 49 out of 159 field strawberry samples via RT-PCR followed by Sanger sequencing. The bacilliform shape of the virions, which have a cytoplasm-limited distribution, their size, and phylogenetic relationships support the assignment of StrV-1 to a distinct species of the genus Cytorhabdovirus. Acyrthosiphon malvae, A. fabae, and A. ruborum were shown to transmit StrV-1 under experimental conditions.